2019
DOI: 10.1007/s00167-019-05429-y
|View full text |Cite
|
Sign up to set email alerts
|

Good 5-year outcomes after arthroscopic treatment for femoroacetabular impingement syndrome

Abstract: Purpose The purpose of the present study was to evaluate the outcome of arthroscopic treatment for femoroacetabular impingement (FAI) syndrome 5 years post-surgery using patient-reported outcome scores (PROMs) validated for a young and active population with hip complaints. Methods Patients were prospectively included in the study. A total of 184 patients [males = 110 (59.8%), females = 74 (40.2%)], with mean age 38.0, underwent arthroscopic treatment for FAI syndrome and were analysed. Preoperatively and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Although some short-term benefits of nonoperative management for FAI have been reported, longitudinal outcomes for athletic patients are lacking. 31 , 33 The literature surrounding surgical treatment for FAI is more extensive, and favorable results with few complications are reported in both general 42 and athletic populations. 25 , 26 , 34 Some predictors of outcomes have been reported previously among general populations.…”
mentioning
confidence: 99%
“…Although some short-term benefits of nonoperative management for FAI have been reported, longitudinal outcomes for athletic patients are lacking. 31 , 33 The literature surrounding surgical treatment for FAI is more extensive, and favorable results with few complications are reported in both general 42 and athletic populations. 25 , 26 , 34 Some predictors of outcomes have been reported previously among general populations.…”
mentioning
confidence: 99%
“…1,40 Arthroscopic treatment for FAIS has become increasingly common during the past decade and has yielded good clinical outcomes. 16,17,31 The purpose of surgical intervention is to reduce pain and increase ROM by removing cam and pincer deformities, striving for impingement-free hip anatomy and improved hip function. The literature also suggests a low rate of complications and reoperations after arthroscopic treatment for FAIS.…”
mentioning
confidence: 99%
“…Our study found that arthroscopic surgery and postsurgical physiotherapy seem to provide effective treatment for femoroacetabular impingement. Öhlin et al conducted a five-year follow-up assessment of treatment results with several scales and had similar results, where 84.6% of their subjects were satisfied with the surgery [ 23 ].…”
Section: Discussionmentioning
confidence: 99%